Beautiful days : stories - Oates, Joyce Carol, 1938- (Ecco, an imprint of HarperCollinsPublishers, 2018)
"A new collection of stories by American master Joyce Carol Oates, mysterious and surreal, and perfectly pitched for the confusion of the current political landscape"--